2022
DOI: 10.1177/02601060221132922
|View full text |Cite
|
Sign up to set email alerts
|

High-protein diets and testosterone

Abstract: A recent meta-analysis found low-carbohydrate, high-protein diets (> 3.4 g/kg of bodyweight/day) (g/kg/day) decreased men's total testosterone (∼5.23 nmol/L) [Whittaker and Harris (2022) Low-carbohydrate diets and men's cortisol and testosterone: systematic review and meta-analysis. Nutrition and Health. DOI: 10.1177/02601060221083079]. This finding has generated substantial discussion, however, it has often lacked clarity and context, with the term ‘high-protein’ being used unqualified. Firstly, diets <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…A mild but significative reduction in serum testosterone has also been observed with the Mediterranean diet [ 80 ]. Conversely, a low-carb diet with moderate-to-high protein intake not exceeding 3.4 g/kg/day is usually associated with a neutral or even ameliorating effect on serum testosterone [ 81 , 82 , 83 ]. Very low-carb diets induce a significant increase in serum testosterone, even if the magnitude of this effect is strictly associated with weight loss and the patient’s age [ 84 ].…”
Section: Preventing Sarcopenia: a Therapeutic Target In Primary And S...mentioning
confidence: 99%
“…A mild but significative reduction in serum testosterone has also been observed with the Mediterranean diet [ 80 ]. Conversely, a low-carb diet with moderate-to-high protein intake not exceeding 3.4 g/kg/day is usually associated with a neutral or even ameliorating effect on serum testosterone [ 81 , 82 , 83 ]. Very low-carb diets induce a significant increase in serum testosterone, even if the magnitude of this effect is strictly associated with weight loss and the patient’s age [ 84 ].…”
Section: Preventing Sarcopenia: a Therapeutic Target In Primary And S...mentioning
confidence: 99%
“…A recent cross-sectional study conducted on 125 Taiwanese men reported that greater adherence to a typical high-calorie WD was associated with a decrease in testosterone levels by 0.87 ng/mL [ 136 ]. Furthermore, a recent meta-analysis by Whittaker and Harris [ 137 ] revealed that very-high-protein diets (>3.4 g/kg/day) are associated with a decrease in men’s total testosterone levels by approximately 5.23 nmol/L. This suggests that adopting hyper-protein diets for weight loss or muscle mass gain might be counterproductive, potentially adversely affecting testosterone levels.…”
Section: Nutritional Impact On Hormonal Regulationmentioning
confidence: 99%